2020
DOI: 10.1186/s13048-020-00635-6
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of NCALD is associated with chemotherapy resistance and poor prognosis in epithelial ovarian cancer

Abstract: Background: Low expression of NCALD(neurocalcin delta) in peripheral blood of ovarian cancer patients predicts poor prognosis. However, the molecular mechanism of NCALD in ovarian cancer and its relationship with chemotherapy outcomes is unclear. The aim of this study was to investigate the potential signaling pathways of NCALD and to evaluate its ability to predict chemotherapy outcomes and prognosis. Methods: High-throughput RNA sequencing data were downloaded from TCGA. GSEA explored the potential signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…AF131215.5 was a lncRNA whose function remained unclear in cancer [ 31 , 32 ]. Interestingly, NCALD (neurocalcin delta) expression was lower in lung adenocarcinoma tissues [ 33 ], and patients with higher NCALD levels exhibited a higher survival rate [ 34 , 35 ]. Among these genes, we hypothesized that NCALD, the tumor suppressor gene, might be a potential target of MIDEAS-AS1 in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AF131215.5 was a lncRNA whose function remained unclear in cancer [ 31 , 32 ]. Interestingly, NCALD (neurocalcin delta) expression was lower in lung adenocarcinoma tissues [ 33 ], and patients with higher NCALD levels exhibited a higher survival rate [ 34 , 35 ]. Among these genes, we hypothesized that NCALD, the tumor suppressor gene, might be a potential target of MIDEAS-AS1 in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies had found that NCALD was not only involved in cell apoptosis, cell cycle progression and other biological processes in several cancers [ 36 ], but also associated with the prognosis of cancers [ 34 , 35 ]. However, there is no report about the function of NCALD in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…KIF1C is a kinesin-like motor protein that mediates the resistance of mouse macrophages to anthrax lethal factor and is currently less studied in tumors ( 34 ). Involved in calcium signaling as well as G protein-coupled receptor signaling, NCALD is part of the neuronal calcium sensor family ( 35 ), and lower expression of NCALD in tumors is also considered to be associated with poor prognosis ( 36 ). GTF3A is considered to be associated with the migration of different types of cancer, and in colorectal cancer, high GTF3A and GTF3B expression seems to be associated with poor prognosis ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reduced NCALD expression was more prevalent in poorly differentiated tumors 94 . Feng et al validated these findings and also outlined that NCALD expression was significantly lower in the tumor tissue from chemoresistant OC patients 95 . Although these studies provided transcriptomic data, neither assessed the relationship between NCALD methylation and gene expression.…”
Section: Main Textmentioning
confidence: 98%
“…validated these findings and also outlined that NCALD expression was significantly lower in the tumor tissue from chemoresistant OC patients. 95 Although these studies provided transcriptomic data, neither assessed the relationship between NCALD methylation and gene expression. To that end, in a more recent study, 450 K Infinium Methylation BeadChip analysis showed that there was greater methylation at three specific CpG sites within the NCALD gene in chemoresistant compared to chemosensitive HGSOC.…”
Section: Ncaldmentioning
confidence: 99%